Design, Dynamic Modelling, Simulation and Control of a Solar Powered Sucker Rod Oil Pump - Osaretin, Charles Aimiuwu; Iqbal, Mohammad Tariq; Butt, Stephen (Journal of Electronics and Electrical Engineering, 2025)
The sucker rod pump is a crucial artificial lift system widely deployed in the oil industry to extract crude oil from producing wells. Accurate modelling of the sucker rod pump has become essential as a viable strategy for optimizing performance, and ensuring both efficient and economic operation. This paper presents a comprehensive methodology for the design, dynamic modelling, simulation, and control of a solar-powered sucker rod oil pump. It combines load modelling of the sucker rod pump using SolidWorks with design, dynamic modelling, simulation, and control of the solar microgrid in Matlab's Simscape and Simulink. The model seamlessly integrates the mechanical and electrical systems with 100% renewable energy to power the sucker rod pump system. This approach combines the solar photovoltaic system, battery charge control system, battery energy storage system, step-up transformer, and the squirrel cage induction motor, which serves as the electric motor prime mover. The surface pump model is first developed in SolidWorks and then converted to Simscape, the rating of the pump is then implemented as a load in the solar-powered electrical microgrid. Environmental conditions such as solar irradiance and ambient temperature for summer and winter are obtained from data repositories and included in the modelling and analysis of the overall system performance demonstrating stable operation, robustness, and resilience to changing environmental and operational conditions.